2013
DOI: 10.1080/07448481.2013.805714
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Alcohol Problems in College Students: The Mediating Effects of Stress

Abstract: Mindfulness-based stress reduction or other mindfulness programs may be useful in decreasing alcohol problems on college campuses via the effects on stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 53 publications
3
30
0
4
Order By: Relevance
“…In this study, only acting with awareness is associated with all three types of alcohol use behaviors, over and above other trait mindfulness facets. Although these findings are consistent with previous work linking acting with awareness with multiple aspects of alcohol use behaviors, including problematic alcohol use (Bodenlos et al, 2013; Leigh and Neighbors, 2009), some studies have found that other trait mindfulness facets are also related to different aspects of alcohol use behaviors (Fernandez et al, 2012; Murphy and MacKillop, 2012). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, only acting with awareness is associated with all three types of alcohol use behaviors, over and above other trait mindfulness facets. Although these findings are consistent with previous work linking acting with awareness with multiple aspects of alcohol use behaviors, including problematic alcohol use (Bodenlos et al, 2013; Leigh and Neighbors, 2009), some studies have found that other trait mindfulness facets are also related to different aspects of alcohol use behaviors (Fernandez et al, 2012; Murphy and MacKillop, 2012). …”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that college students with higher levels of overall trait mindfulness might be at reduced risk for developing problematic levels of alcohol use (Bodenlos et al, 2013; Ostafin and Marlatt, 2008), but might not necessarily have lower rates of alcohol use quantity and duration. At the same time, college students who specifically have higher levels of acting with awareness might be at lower risk for developing problematic levels of alcohol use, likely through reduced alcohol consumption in general (Fernandez et al, 2010; Leigh and Neighbors, 2009; Murphy and MacKillop, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This could account for the overall small relationship between trait mindfulness and substance use behaviors found in prior studies. Indeed, the five facets of mindfulness have been shown to be differentially related with substance use behaviors—with acting with awareness, non-judgment, and non-reactivity being the facets most frequently related to reduced substance use behaviors (Bodenlos et al, 2013; Fernandez et al, 2010; Leigh and Neighbors, 2009; Murphy and MacKillop, 2012). Additionally, trait mindfulness might be differentially related to distinct substance use behaviors (Black et al, 2011; Fernandez et al, 2010; Robinson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…La evaluación permite detectar e intervenir en posibles señales o respuestas de estrés ante las situaciones de estudio o de la oposición. Existes numerosos tratamientos comportamentales para desactivar las respuestas de estrés fisiológico que son interferentes con el estudio o peligrosas para la salud, como la numerosa evidencia existente ha mostrado (Bodenlos, Noonan y Wells, 2013;Davis, McKey y Eshelman, 1985).…”
Section: Estrés Fisiológico Y Motorunclassified